Model Snowball Drilling untuk Meningkatkan Hasil Belajar Siswa - Lestari, Indah; Mahmudah, Muhlisatul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2021)
This research aims to improve student learning outcomes in studying social arithmetic using the application of the snowball drilling learning model. The type ofstudy uses is Classroom Action Assessment (PTK), with research procedures using a cycle model, from the results of the study in cycle I the percentage of student learning outcomes reached 64% and cycle II was 100%. This proves that the level of understanding of students increases with the application of the snowball drilling model, so that learning can provide an overview with examples of basic illustrations. This combination is used for teaching that can best illustrate with examples of basic illustrations